Tante Stella’s Quince Sweetmeat - Levy, Audrey (Petits Propos Culinaires, 2007)
A survey of the history of the quince in Europe including appearances in English literature along with descriptions of some famous concoctions such as brimbriyo (Sephardic), cotognata (Sicily), cotignac (France), membrillo (Spain), kythonpasto (Greece).